Pharmacologic screen identifies active combinations with BET inhibitors and LRRK2 as a novel putative target in lymphoma - Filippo Spriano; Giulio Sartori; Chiara Tarantelli; Marilia Barreca; Gaetanina Golino; Andrea Rinaldi; Sara Napoli; Michele Mascia; Lorenzo Scalise; Alberto J. Arribas; Luciano Cascione; Emanuele Zucca; et al. (eJHaem, 2022)
Abstract Inhibitors of the Bromo‐ and Extra‐Terminal domain (BET) family proteins have strong preclinical antitumor activity in multiple tumor models, including lymphomas. Limited single‐agent activity has been reported in the clinical setting. Here, we have performed a pharmacological screening to identify compounds that can increase the antitumor activity of BET inhibitors in lymphomas. The germinal center B‐cell like diffuse large B‐cell lymphoma (DLBCL) cell lines OCI‐LY‐19 and WSU‐DLCL2 were exposed to 348 compounds given as single agents at two different concentrations and in combination with the BET inhibitor birabresib. The combination partners included small molecules targeting important biologic pathways such as PI3K/AKT/MAPK signaling and apoptosis, approved anticancer agents, kinase inhibitors, epigenetic compounds. The screening identified a series of compounds leading to a stronger antiproliferative activity when given in combination than as single agents: the histone deacetylase (HDAC) inhibitors panobinostat and dacinostat, the mTOR (mechanistic target of rapamycin) inhibitor everolimus, the ABL/SRC (ABL proto‐oncogene/SRC proto oncogene) inhibitor dasatinib, the AKT1/2/3 inhibitor MK‐2206, the JAK2 inhibitor TG101209. The novel finding was the benefit given by the addition of the LRRK2 inhibitor LRRK2‐IN‐1, which was validated in vitro and in vivo. Genetic silencing demonstrated that LRRK2 sustains the proliferation of lymphoma cells, a finding paired with the association between high expression levels and inferior outcome in DLBCL patients. We identified combinations that can improve the response to BET inhibitors in lymphomas, and LRRK2 as a gene essential for lymphomas and as putative novel target for this type of tumors.